1999
DOI: 10.1093/jn/129.2.544s
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intergenerational Effects on Linear Growth

Abstract: Current knowledge on the role of intergenerational effects on linear growth is reviewed on the basis of a literature search and recent findings from an ongoing study in Guatemala. Fourteen studies were identified, most of which examined the intergenerational relationships in birth weight. Overall, for every 100 g increase in maternal birth weight, her child's birth weight increased by 10-20 g. The study samples were primarily from developed countries, and birth weight data were extracted from hospital records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
124
0
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(148 citation statements)
references
References 24 publications
17
124
0
5
Order By: Relevance
“…Nevertheless, it is still an important novel finding, especially since we found that birth length was significantly associated with HLA genotypes. In our study, MPH SDS were taken into consideration when we analysed intrauterine and childhood growth, since birth length, birthweight and childhood linear growth are strongly correlated with the height of the parents [21,22,38]. Therefore it is important to correct for MPH when analysing growth parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it is still an important novel finding, especially since we found that birth length was significantly associated with HLA genotypes. In our study, MPH SDS were taken into consideration when we analysed intrauterine and childhood growth, since birth length, birthweight and childhood linear growth are strongly correlated with the height of the parents [21,22,38]. Therefore it is important to correct for MPH when analysing growth parameters.…”
Section: Discussionmentioning
confidence: 99%
“…However, our data did not support this hypothesis and indicate that factors other than high-risk HLA are responsible for this increased growth rate in children developing diabetes. In this prospective study we examined the growth pattern of a cohort of children developing diabetes before 6 years of age compared with controls matched for HLA genotypes and corrected for MPH since this is strongly associated with the linear growth of children [21,22,38]. Previous studies have reported a relationship between high birthweight and both low-risk [39] and high-risk [14,15] HLA genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entretanto, a maior limitação é baseada nos termos éticos, já que esse tipo de estudo exigiria um grupo controle que não recebesse o tratamento padrão, já que muitos países já adotam como rotina a suplementação de ferro para gestantes, em função do aumento do requerimento desse nutriente conforme recomendações internacionais da OMS 1 . Assim, sugere-se que estudos prospectivos sejam realizados em países em desenvolvimento que enfoquem o impacto do uso do suplemento e do padrão dietético no prognóstico da gestação e indicadores bioquímicos 25 .…”
Section: Discussionunclassified
“…There is a well-recognised 'intergenerational cycle of growth failure' in the developing world -young girls who grow poorly become stunted women and are more likely to give birth to low birth weight babies. If these infants are girls, they are likely to continue the cycle by being stunted in adulthood and so on (Ramakrishnan et al 1999). Could this apparent intergenerational effect on fetal growth also be important in the developed world?…”
Section: Introduction: the Early Life Origins Of Diseasementioning
confidence: 99%